Emotional Intelligence and Critical Thinking in Nursing Students: A Systematic Literature Review - Sihaloho, Roy Wilson (Sean Institute, 2022)
To investigate the emotional intelligence and critical thinking of nursing students. Emotional intelligence and critical thinking are basic elements of nursing practice and are involved in making decisions in nursing clinical practice, using evidence and information in practice and ensuring the quality of safe and effective services. systematic review of literature, article search through electronic databases (Scien direct, PunMed, BMC Nursing and ProQuest). Articles searched in English or Indonesian between 2012 – 2023. The article review process uses the PRISMA protocol. A total of 5 articles were used for review, the literature focused on emotional intelligence and critical thinking in nursing students. This literature review states that there is a relationship between emotional intelligence and critical thinking in nursing students. Nursing students with critical thinking skills and good emotional intelligence will be more successful in their education and find work more easily. Emotional intelligence and critical thinking can be learned and can be improved through active learning methods and student-centered learning methods.